Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja UMKM (Studi Kasus pada UMKM di Kabupaten Karawang Tahun 2021) - Aina Farhani; Endang Taufiqurahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the influence of financial literacy and financial inclusion on the performance of of Micro Small and Medium Enterprises (MSMEs) in Karawang Regency. The research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. Sampling using probability sampling. The analytical technique used is the technique of scale range analysis and path analysis with the help of the Method of Successive Interval (MSI), the Microsoft Excel 2010 computer program and the SPSS version 25 application. Based on the results of the analysis that has been carried out, this study proves that Financial Literacy shows an average value of 1,570 with agreed criteria. Financial Inclusion shows an average score of 1,558 with the criteria for agreeing. MSME performance shows an average value of 1,556 with agreed criteria. The correlation coefficient between the variables of Financial Literacy and Financial Inclusion obtained a value of 0.924 which means it has a very strong, positive and significant correlation level between Brand Image and Price. The partial effect of Financial Inclusion on MSME Performance is 0.432, which is greater than Financial Literacy which is 0.418. So it can be stated that Financial Inclusion contributes more to MSME Performance compared to Financial Literacy. The simultaneous effect of Financial Literacy and Financial Inclusion on MSME Performance is 8% while the remaining 15% is another variable that is not examined. Keywords : Financial Literacy, Financial Inclusion, Perfomance MSMEs